Detection of Multidrug Resistant (MDR) and Extremely Drug Resistant (XDR) P. Aeruginosa Isolated from Patients in Tehran, Iran - Saderi, Horieh (Iran J Pathol, 2015)
BACKGROUND: This study was done to detect multidrug resistant (MDR) and extremely drug resistant (XDR) of Pseudomonas aeruginosa among strains isolated from patients in Tehran, Iran, due to importance of these phenotypes in treatment of human infections. METHODS: Eighty eight P. aeruginosa were isolated from patients in Tehran, Iran, and identified by routine methods and PCR for oprL gene. Their antimicrobial susceptibility to 16 antimicrobial agents from 7 antimicrobial categories (aminoglycosides, carbapenems, cephalosporins, fluoroquinolones, penicillins/ß-lactamase inhibitors, monobactams, polymyxins) were determined by disk diffusion method, according to recommendation of Clinical and Laboratory Standards Institute. Characterization of P. aeruginosa isolates as MDR and XDR was done according to standardized international terminology presented by European Centre for Disease Prevention and Control as well as the Centers for Disease Control and Prevention in 2011. MDR was defined as acquired non-susceptibility to at least one agent in ≥3 antimicrobial categories and XDR was defined as non-susceptibility to at least one agent in ≥6 antimicrobial categories. RESULTS: The rates of susceptibility to antimicrobials were as follows: gentamicin 27.3%, tobramycin 54.5%, amikacin 56.8%, netilmicin 36.4%, imipenem 55.7%, meropenem 55.7%, doripenem 60.2%, ceftazidime 63.6%, cefepime 56.8%, ciprofloxacin 59.1%, levofloxacin 60.2%, ticarcillin-clavulanic acid 37.5%, piperacillin-tazobactam 63.6%, aztreonam 43.2%, colistin 90.9%, polymyxin 95.5%. Altogether, 48 (54.5%) and 29 (33%) isolates were characterized as MDR and XDR, respectively. DISCUSSION: The high frequency of antibiotic resistance in clinical isolates of P. aeruginosa in Iran makes epidemiological surveillance of susceptibility of this bacterium more essential for the best selection of empirical antibiotics.